Culture of Chlorella ellipsoidea in different culture media (International Journal of Agricultural Research, Innovation and Technology, 2017)
An experiment of algal culture was conducted in natural light and temperature conditions at a balcony of a room at the 2nd floor of Fisheries Faculty Building facing the north. The experiment was done to evaluate the growth of Chlorella ellipsoidea in four different media, viz, medium I (inorganic), medium II (organic, whole pulse powder extract), medium III (organic, whole lentil powder extract) and medium IV (organic, whole gram powder extract) under natural environment conditions during January-June, 2015. Growth rates of the algal species in four different media were found not significantly different. The alga, C. ellipsoidea attained maximum cell density of 28.89×106 cell ml-1 in the 15th day in medium I, of 30.69×106 cell ml-1 in the 13th day in medium II, of 26.18×106 cell ml-1 in the 15th day in medium III and of 21.12×106 cell ml-1 in the 13th day in medium IV. The ranges of air temperature, water temperature and light intensity were 21°C to 38°C, 23°C to 36°C and 2.28×103to 9.60×103 Lux respectively during the culture period. The average sunshine period was 5.87±2.82 hrs. Total alkalinity, free CO2, pH , NO3-N and PO4-P of algal culture media I, II, III and IV were 128, 540, 554 and 322 mgL-1; 32, 162, 102, 70 mgL-1; 7.4, 8, 7.9 and 7.9; 180, 36.6, 62.4 and 150 mgL-1, and 25.2, 48.2, 42.4 and 45.6 mgL-1, respectively. According to ANOVA of cell densities of cultures of C. ellipsoidea under treatments are not significantly different (F=1.441077). It is clear that differences between them are not significant i.e. mean algal cell densities are more or less same as differences between treatments are less than 20%.Int. J. Agril. Res. Innov. & Tech. 7 (1): 51-57, June, 2017